Therapeutic potential of azithromycin in rosacea - (:unkn) unknown (WILEY, 2004)
Background Systemic antibiotics currently used in the treatment of rosacea are sometimes associated with uncomfortable side-effects. Therefore, a need for an effective agent with few side-effects and good patient compliance exists. Azithromycin, a macrolide antibiotic with prolonged mode of action, has recently been found to be an effective alternative in the treatment of inflammatory acne. We planned a study to evaluate the efficacy and safety of azithromycin in rosacea. Methods An open-labeled study was performed in a population of 18 patients, with Plewig-Kligman stage 2 rosacea. Patients were given oral azithromycin for 12 weeks in decreasing doses. Results Fourteen subjects completed the trial. The treatment produced therapeutic benefits with regard to total scores as well as inflammatory lesion scores. At the end of 12 weeks, there was a 75% decrease in total scores (P < 0.001) and an 89% decrease in inflammatory lesion scores compared with basal values. Improvement continued during the 4 weeks after treatment. Adverse effects were minimal and well tolerated in most patients. Conclusion Azithromycin is a promising agent in the treatment of rosacea with its few side-effects and good patient compliance.